Building Better Teachers: The Constructivist Influence of Cooperative Mentors in Early Childhood Fieldwork - Al-Hassan, Omayya M.; AlAli, Rommel Mahmoud; Al-Barakat, Ali Ahmad; Zaher, Ashraf Mahrous (Journal of Posthumanism, 2025)
This study explores the role of cooperating mentors in promoting constructivist learning practices among pre-service early childhood education teachers during their field experience. Constructivist learning emphasizes active, self-directed learning, critical thinking, and social interaction. Data were gathered using the Cooperating Mentor Behavior Assessment Tool from 210 pre-service teachers in field education programs at public universities. The findings revealed that cooperating mentors supported practices such as encouraging children to share ideas and connecting lessons to prior knowledge. However, gaps were identified in areas like uncovering children’s prior knowledge, facilitating knowledge construction, and using assessments to enhance learning. The study also found no significant relationship between pre-service teachers’ evaluations of mentors’ roles and factors such as academic performance, teaching experience, or mentor qualifications. The study concludes with recommendations to improve the implementation of constructivist practices in teacher education.